How regional innovation and entrepreneurship vitality affects residents’ leisure consumption potential—utility differences between educational investment and scientific and technological investment - Yunying Cai; Wenhe Lin; Jinfa Zhong; Qiqi Hu; Yaqing You (PLoS ONE, 2025)
Innovation and entrepreneurship vitality, as a key factors in the development of the digital economy, significantly affects both regional economic development and residents’ consumption capacity. On the basis of the panel data of 31 provinces and cities in China from 2010 to 2022, this paper explores the impact of regional innovation and entrepreneurship vitality on residents’ leisure consumption potential and its internal mechanism. Research has shown that innovation and entrepreneurship vitality drives leisure consumption potential. Furthermore, regional innovation and entrepreneurship vitality can effectively increase educational investment, which in turn increases residents’ leisure consumption potential. Although scientific and technological investment can significantly increase innovation and entrepreneurship vitality, it curtails the development of residents’ leisure consumption potential. In addition, there are significant differences in the effect of regional innovation and entrepreneurial vitality on residents’ leisure consumption potential in different policy environments and demographic structure. Diverse policies help to better stimulate regional innovation and entrepreneurship influence on residents’ leisure consumption. The development of innovation and entrepreneurship vitality can effectively stimulate the leisure consumption potential of residents in areas with low population mobility, which compensate for the decrease of leisure consumption due to the lack of external population. On the basis of the inconsistency between economic development and residents’ spiritual needs in China’s major contradictions, this study further explores the coordination between scientific and technological development and individuals’ needs for a better life, and further complements and justifies the literature in the field of innovation and consumption.